Strengthening Teachers' Digital Literacy through Training in Wordwall-Based Learning Media - Indah Hapsari Ningsih; Masada Mukti Aditiaputri; Tiara Selviamita; Anton Adi Suryo Kusuma (JARDIRA – Jurnal Pengabdian Digital dan Rekayasa Informatika, 2026)
Background: Advances in information technology require teachers to possess adequate digital literacy skills to design innovative learning experiences that meet the needs of twenty-first-century students. However, limited access to training and technical mentoring has prevented the optimal use of digital learning technologies in elementary schools.Contribution: This community service program aimed to strengthen teachers’ digital literacy by introducing Wordwall as an interactive learning and assessment platform. The program also supported teachers in independently developing digital learning media that could be adapted to different instructional needs.Method: The program was conducted at MI Muhammadiyah Wonorejo through three main stages: socialization on the importance of digital literacy, practical training in the use of the Wordwall platform, and technical mentoring in the development of interactive learning media. Program effectiveness was evaluated using pre-tests, post-tests, observations, documentation, and assessments of the learning media created by participants.Results: The average level of teachers’ digital literacy competence increased from 35% to 80.5%, representing an improvement of 45.5 percentage points. Furthermore, 80% of the teachers were able to independently create Wordwall-based learning media, 70% were able to modify templates according to instructional needs, and 65% had begun using Wordwall as a learning evaluation tool.Conclusion: Training combined with continuous technical mentoring effectively strengthened teachers’ digital literacy, practical skills, and confidence in using educational technology. The program also encouraged the development of more interactive, innovative, and technology-enhanced learning practices in elementary education